Innate immune signalling, neuroinflammation and network plasticity in temporal lobe epilepsy - Arias-Carrión, Oscar; Rodríguez de Ita, Julieta; Yu, Philipp (Frontiers in Pharmacology, 2026)
Temporal lobe epilepsy emerges from a cascade of molecular, cellular, and structural disturbances triggered by heterogeneous cerebral insults—including convulsive status epilepticus, viral encephalitis, traumatic brain injury, and blood–brain barrier disruption—that converge on progressive hippocampal reorganization and a chronic predisposition to unprovoked focal seizures. Convergent evidence from chemoconvulsant models, focal intrahippocampal kainate administration, viral encephalitis paradigms, organotypic hippocampal cultures, human iPSC-derived organoids, and resected human tissue shows that innate immune pathways are not secondary epiphenomena but central drivers of epileptogenesis. Pattern-recognition receptors—particularly TLR2, TLR3, TLR4, IL-1R1 and the NLRP3 inflammasome—sense pathogen- and damage-associated molecular motifs, including HMGB1, and initiate MyD88-, NF-κB- and caspase-1–dependent signaling. These cascades acutely amplify IL-1β, TNF-α and IL-6 responses, alter ion-channel phosphorylation states, enhance NMDA- and AMPA-receptor–mediated excitation, and impair GABAergic inhibition, thereby lowering the seizure threshold. Sustained innate immune activation drives microglial M1 polarization, complement-mediated synaptic loss, aberrant neurogenesis, endothelial dysfunction, and persistent astroglial reactivity—mechanisms that reinforce circuit hyperexcitability and enable the transition from provoked to spontaneous recurrent seizures. Targeted interventions—including TLR4 antagonists (TAK-242), IL-1–pathway inhibitors (anakinra; the caspase-1 inhibitor VX-765), NLRP3 inhibitors (MCC950), and complement-directed strategies—reduce seizure burden, mitigate hippocampal atrophy, and, when administered early, attenuate maladaptive network remodeling. Several conventional antiseizure medications, including levetiracetam, also exhibit immunomodulatory properties by modulating microglial activation, suggesting a mechanistic overlap between pharmacological seizure control and immune regulation. Emerging data implicate the TLR7–endogenous retrovirus axis as an upstream determinant of neuroimmune homeostasis, linking impaired surveillance of viral and retroelement activity to glial activation and network instability. Together, these findings position innate immunity as a mechanistically coherent and therapeutically tractable axis in temporal lobe epilepsy. Achieving clinical translation will require immune-phenotype stratification, biomarker-guided timing of intervention, and advances in CNS-targeted delivery. Integrating immunomodulatory approaches with established antiseizure therapies offers a promising route toward disease modification, cognitive preservation, and more precise treatment of drug-resistant epilepsy.